RECHALLENGING TREATMENT PLAN FOR MULTIDRUG-RESISTANT TUBERCULOSIS IN DIABETIC PATIENT: A CASE REPORT - AL-TEMIMI, AHMED ALAA; M NIZAM, MUHAMMAD ZHARIF; HASSAN, YAHAYA; A AZIZ, NOORIZAN; MOHD ASMANI, MOHD FADLI; ABDULLAH, IBRAHIM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Multidrug-resistant tuberculosis (MDR-TB) currently considers as the biggest issue and its subcategory, rifampicin-resistant TB (RR-TB). MDR-TB is defined as a resistant to isoniazid (H) and rifampicin (R), while the latter is resistant to rifampicin (R) only. Poorly controlled diabetes mellitus increases the risk of TB and leads to poor TB treatment outcomes as well it is consider potentially threating TB control. Difference in patients’ response and side effect developments toward anti-TB (ATB) medications requires rechallenging procedure that can be complicated at times. The management of MDR-TB can be complicated, especially, when the patient cannot tolerate the short regimen. Difference in patients’ response and side effect developments toward ATB medications requires rechallenging procedure which can have prolonged treatment time, hospital stay, and make patients exposed to hospital-acquired infection. This challenges and obstacles, however, could be prevented earlier by having strong DOTS strategy to prevent the development of resistance and reactivation of TB.